2023
DOI: 10.1101/2023.04.28.538737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The trade-off between individual metabolic specialization and versatility determines the metabolic efficiency of microbial communities

Abstract: In microbial systems, a metabolic pathway can be either completed by one autonomous population or alternatively be distributed among a consortium performing metabolic division of labor (MDOL), where several specialized populations cooperate to complete the pathway. MDOL facilitates the system's function by reducing the metabolic burden; however, it may also hinder the function by reducing the exchange efficiency of metabolic intermediates among individuals. As a result, the metabolic efficiency of a community … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…62−64 A recent study has shown that metabolic redundancy within a DOL system can be beneficial by balancing the trade-offs between metabolic specialization (such as in SDOL) and generality (such as in monoculture). 65 Wang et al engineered 1,456 unique microbial consortia for the degradation of naphthalene. Each consortium was constructed of strains carrying parts of the naphthalene degradation pathway, with each part of the pathway covered by at least one strain.…”
Section: ■ Discussionmentioning
confidence: 99%
“…62−64 A recent study has shown that metabolic redundancy within a DOL system can be beneficial by balancing the trade-offs between metabolic specialization (such as in SDOL) and generality (such as in monoculture). 65 Wang et al engineered 1,456 unique microbial consortia for the degradation of naphthalene. Each consortium was constructed of strains carrying parts of the naphthalene degradation pathway, with each part of the pathway covered by at least one strain.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 3, 2023. ; https://doi.org/10.1101/2023.10.03.560696 doi: bioRxiv preprint A recent study has shown that metabolic redundancy within a DOL system can be beneficial by balancing the tradeoffs between metabolic specialization (such as in SDOL) and generality (such as in monoculture) (59). Wang et al engineered 1,456 unique microbial consortia for the degradation of naphthalene.…”
Section: Discussionmentioning
confidence: 99%